KETIDAKADILAN GENDER DALAM NOVEL DI BAWAH LINDUNGAN KA'BAH KARYA BUYA HAMKA: KAJIAN FEMINISME LIBERAL - Salamudin, Faisal Salmi; Encep Suherman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the existence of gender inequality in literary works, which is often influenced by patriarchal culture. The novel Di Bawah Lindungan Ka'bah by Buya Hamka portrays the life of women within strong social and cultural constraints. This research aims to identify and describe the forms of gender injustice and feminist values contained in the novel. The study employs a qualitative descriptive method with a library research approach. Data were collected using a hermeneutic technique, involving reading, note-taking, and interpreting relevant excerpts related to feminist analysis. The results show that there are various forms of gender inequality experienced by female characters, such as restrictions on mobility through the seclusion tradition, limited access to education, and family dominance in determining marriage decisions. The character of Zainab is portrayed as a woman constrained by patriarchal social and cultural norms, limiting her autonomy in making life choices. The study also finds elements of liberal feminism that emphasize the importance of equal rights between men and women, particularly in social and educational aspects. In conclusion, the novel not only presents a romantic story but also reflects the social reality of women's position in society. This research is expected to contribute to the development of literary studies, especially in feminist literary criticism.